1986
DOI: 10.1111/j.1469-8137.1986.tb00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Tansley Review No. 5 Fructans and the Metabolism of Sucrose in Vascular Plants

Abstract: SUMMARY The occurrence, structure and metabolism of fructose polymers in tissues of vascular plants are discussed in relation to the metabolism of sucrose. Distinctions are made between long‐term and short‐term storage of such polymers and the regulatory mechanisms which govern accumulation are examined. The roles of various fructosyltransferases in the synthesis of the different fructan structures from sucrose are outlined. The potential selective advantages of the possession of fructan metabolism in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
191
3
10

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(220 citation statements)
references
References 103 publications
10
191
3
10
Order By: Relevance
“…Inulin molecules are polymers in which adjacent fructose residues are joined by 13-2,1 linkages whereas levan-type fructans are characterized by 13-2,6 bonds linking the fructosyl units (Pollock, 1986;Pollock and Cairns, 1991;Pollock and Chatterton, 1988). However, besides linear fructans many plants also store branched molecules of different linkage types (Housley and Pollock, 1993;Pollock, 1986;Pollock and Cairns, 1991;Pollock and Chatterton 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Inulin molecules are polymers in which adjacent fructose residues are joined by 13-2,1 linkages whereas levan-type fructans are characterized by 13-2,6 bonds linking the fructosyl units (Pollock, 1986;Pollock and Cairns, 1991;Pollock and Chatterton, 1988). However, besides linear fructans many plants also store branched molecules of different linkage types (Housley and Pollock, 1993;Pollock, 1986;Pollock and Cairns, 1991;Pollock and Chatterton 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Since fructo-oligosaccharide accumulation is frequently correlated with plants exposed to low temperatures, it has been suggested that fructans may act as cryoprotectants (Eagles 1967, Wiemken et al 1986, Pollock & Chatterton 1988. Corroborating this hypothesis is the fact that grasses including cereals (wheat, oats and barley) accumulate fructans during winter (Meier & Reid 1982, Pontis & Del Campillo 1985, Pollock 1986, Chatertton et al 1989, Prud'home et al 1993. Also, several species of Asteraceae, as exemplified by chicory (Cichorium intybus L.), accumulate fructans of low degree of polymerization (DP) when exposed to chilling temperatures ( Van den Ende et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in fructan contents and composition have been associated not only with the plant growth but also with seasonal changes in temperature and other environmental factors (Pollock 1986, Pontis 1989, Housley & Pollock 1993, and references there in). Since fructo-oligosaccharide accumulation is frequently correlated with plants exposed to low temperatures, it has been suggested that fructans may act as cryoprotectants (Eagles 1967, Wiemken et al 1986, Pollock & Chatterton 1988.…”
Section: Introductionmentioning
confidence: 99%
“…For plants which suffer from oxygen deprivation (hypoxia), the carbohydrate supply can be of particular importance to cope with this environmental stress. Temperate grasses like wheat {Tri-ticum aestivum L.) are known to accumulate fructans mainly of low DP in vegetative tissues (Bancal & Gaudillere, 1989), whereas starch is deposited in the seeds and to lesser extent in leaf ehloroplasts (Pollock, 1986). The purpose of this article is to show how oxygen deficiency affects carbohydrate balance, especially in relation to fructans.…”
Section: Introductionmentioning
confidence: 99%